The development of attentional control mechanisms in multisensory environments - Turoman, Nora; Tivadar, Ruxandra I.; Retsa, Chrysa; Maillard, Anne M.; Scerif, Gaia; Matusz, Pawel J. (Developmental cognitive neuroscience, 2021)
•By age 7, children show adult-like task-set contingent attentional capture in behavior (top-down visual attentional control).•Children showed no behavioral evidence for multisensory enhancement of attention capture by visual objects paired with sounds.•But 9-year-olds adult-like EEG topographic patterns, differing when elicited by multisensory vs. purely visual distractors.•Traditional N2pc analyses showed no N2pc component in any of the children groups, and no multisensory modulations in adults.•Electrical neuroimaging of well-known ERP components is more sensitive to developmental change in neurocognitive processes. Outside the laboratory, people need to pay attention to relevant objects that are typically multisensory, but it remains poorly understood how the underlying neurocognitive mechanisms develop. We investigated when adult-like mechanisms controlling one’s attentional selection of visual and multisensory objects emerge across childhood. Five-, 7-, and 9-year-olds were compared with adults in their performance on a computer game-like multisensory spatial cueing task, while 129-channel EEG was simultaneously recorded. Markers of attentional control were behavioural spatial cueing effects and the N2pc ERP component (analysed traditionally and using a multivariate electrical neuroimaging framework). In behaviour, adult-like visual attentional control was present from age 7 onwards, whereas multisensory control was absent in all children groups. In EEG, multivariate analyses of the activity over the N2pc time-window revealed stable brain activity patterns in children. Adult-like visual-attentional control EEG patterns were present age 7 onwards, while multisensory control activity patterns were found in 9-year-olds (albeit behavioural measures showed no effects). By combining rigorous yet naturalistic paradigms with multivariate signal analyses, we demonstrated that visual attentional control seems to reach an adult-like state at ∼7 years, before adult-like multisensory control, emerging at ∼9 years. These results enrich our understanding of how attention in naturalistic settings develops.